1987
DOI: 10.1029/jb092ib09p08885
|View full text |Cite
|
Sign up to set email alerts
|

Ice dynamics at the mouth of ice stream B, Antarctica

Abstract: Field data collected at the mouth of Ice Stream B show that the flow dynamics of this region are distinctly different than either the major portion of the ice stream upstream or the ice shelf downstream. Surface slopes in this region are as low as ice shelf surface slopes, yet with the exception of patches of ice which may be floating, the ice is grounded. Basal shear stress is negligible, the resistance to flow being partitioned between shear at the sides and longitudinal gradients of longitudinal and transve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
3

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(108 citation statements)
references
References 29 publications
3
102
3
Order By: Relevance
“…The link between surface strand cracks and tidal flexure, and their opening and closing with the ocean tides, led to the use of observations of surface strand cracks (typically 0.001 to 0.01 m wide and extending for kilometers) to identify or confirm the position of the grounding line for some ice shelves (e.g., Bindschadler, 1993;Bindschadler et al, 1987;Horgan & Anandakrishnan, 2006;Thomas et al, 1988).…”
Section: Tide-induced Fracturesmentioning
confidence: 99%
“…The link between surface strand cracks and tidal flexure, and their opening and closing with the ocean tides, led to the use of observations of surface strand cracks (typically 0.001 to 0.01 m wide and extending for kilometers) to identify or confirm the position of the grounding line for some ice shelves (e.g., Bindschadler, 1993;Bindschadler et al, 1987;Horgan & Anandakrishnan, 2006;Thomas et al, 1988).…”
Section: Tide-induced Fracturesmentioning
confidence: 99%
“…Alley (1993) suggested that Ice raft 'a' (an elliptical feature 10 km by 5 km and a few metres high, near the mouth of Ice Stream B: cf. Bindschadler et al, 1987), might be an obvious candidate for this type of sticky spot. Elsewhere, under Ice Stream C, it was suggested that areas of well drained ('stickier') till of the order of 10 2 m 2 generated micro-earthquakes (Anandakrishnan and Bentley, 1993;Anandakrishnan and Alley, 1994).…”
Section: In Search Of Ice Stream Sticky Spotsmentioning
confidence: 99%
“…The longest time series is available at stake M0 (1963 to 2011) due to an average velocity determined from feature tracking between 1963 DISP and 1997 RADARSat [ Joughin et al , ]. The greatest rate of change reported by Joughin et al [] most closely matches observations made at F7 in the 1970s [ Thomas et al , ] and at M0 in the 1980s [ Bindschadler et al , ; Whillans et al , ]. Although F7 and M0 are nearly 50 km apart, the difference in velocities, as estimated from InSAR data sets, is less than 4 m/yr, considerably smaller than the uncertainty in these earlier observations (± 25 m/yr) [ Bindschadler et al , ].…”
Section: Velocity Estimatesmentioning
confidence: 99%